Woman with a purple heart based on true events - Hanks, Diane (Naperville, Illinois Sourcebooks Landmark, 2023)
"Based on the real life of Lieutenant Annie Fox, Chief Nurse of Hickam Hospital, The Woman with a Purple Heart is an inspiring WWII novel of heroic leadership, courage, and friendship that also exposes a shocking and shameful side of history. Annie Fox will stop at nothing to serve her country. But what happens when her country fails her? In November 1941, Annie Fox, an Army nurse, is transferred to Hickam Field, an air force base in Honolulu. The others on her transport plane are thrilled to work in paradise, but Annie sees her new duty station as the Army's way of holding the door open to her retirement. But serving her country is her calling and she will go wherever she is told. On December 7, Annie's on her way to work when the first Japanese Zero fighter plane flies low over Hickam's Parade Ground. The death and destruction that follow leave her no time to process what's happening. She rallies her nurses, and they work to save as many lives as they can. But soon their small hospital is overwhelmed. Annie drives into Honolulu to gather supplies, nurses, and several women who will donate blood. However, the nurses are Japanese Americans, and the blood donors are prostitutes. Under Annie's leadership and working together in unexpected ways, they make it through that horrific day, when one of the Japanese American nurses and Annie's friend, Kay, is arrested as a suspected subversive. As Hickam tries to recover, Annie works to find her friend and return Kay to her family. But Annie's love for her country is put to the test. How can she reconcile the American bravery and resilience she saw on December 7 with the prejudice and injustice she witnesses just a few months later?"--
Includes reading group guide and a conversation with the author (pages 332-338).
Includes bibliographical references.
112539
Keywords: Fox, Annie -- 1893-1987 -- Fiction; 1939-1945; World War, 1939-1945 -- Participation, Female -- Fiction; Nurses -- United States -- Hawaii -- Fiction; Pearl Harbor (Hawaii), Attack on, 1941 -- Fiction; Military participation -- Female; Biographical fiction; Fiction; Historical fiction; Novels